Is crime analysis at the heart of policing practice?: a case study - Belur, Jyoti (Policing and society, 2018)
Following the introduction of National Intelligence Model (NIM) in 2004, this paper explores whether crime analysis has been integrated into policing practice. Fieldwork was conducted in one UK police force with both analysts and police officers. Findings from the analysis of semi-structured interviews and focus group discussions suggest that while crime analysis is acknowledged as being central to the business of everyday policing, police officers’ general lack of understanding of how analysts work and their capability leads to underutilisation of their skills. The research uncovered knowledge and process gaps, deepened by cultural constraints, budget cuts and resource reallocations, which inhibited incorporation of analysis into the heart of policing practice. Findings also indicated that analysts lack the resources, time, and sometimes, motivation to undertake sophisticated analysis, and often feel frustrated when officers’ opinions override analytical wisdom. The paper argues that at least in the UK, better training and cultural change are necessary for creative utilisation of analytical resources and for bridging the knowledge and process gaps in the organisation.